Strategi Pemasaran Pt X Dalam Meningkatkan Penjualan - Sudiman Sudiman (Universitas Tarumanagara, 2019)
Aim of this thesis is to analyze PT X, a chemical distribution company, and find which strategy can help this company increase sales and survive in competition. First with analyzes the external environmental conditions and advantages possessed by PT X. Then with the SOAR method combine with Offensive and Defensive Competitive Strategy, position and strategy for PT X can be determine. This strategy can help PT X maximize internal strength and take advantages of existing opportunities from external to meet the aspirations and wishes of stakeholders. The conclusion of this thesis found that PT X is follower and need to use attack strategy, which can increase market share. Increase number of customers, increase type of products, and improve service also key factors which can make PT X increase sales.